2021
DOI: 10.1002/app.51900
|View full text |Cite
|
Sign up to set email alerts
|

Construction of novel regenerated cellulose based foam derived from waste cigarette filters as effective oil adsorbent

Abstract: The reuse of waste cigarette filters is helpful to save resources and protect environment, and cellulose based functional materials can be applied in wastewater treatment due to the high porosity. Therefore, a novel kind of cellulose foams were fabricated by using waste cigarette filters and polyvinyl alcohol via a lyophilization technology and hydrophobicity modification in this work.As-prepared foams possessed an ultra-low density and high specific surface area (up to 40 m 2 g À1 ). After the hydrophobicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Furthermore, this group synthesized porous MXene/SWCNTs film as a CDI electrode for the removal of organic dyes in wastewater ( Figure 5 f–j), and the maximum adsorption capacity was as high as 28,403.7 mg/g when applying −2.4 V voltage [ 106 ]. In addition, our group prepared carbon foam electrodes derived from waste cigarette filters/zeolitic-imidazolate frameworks-8 (ZIF-8) composites [ 6 , 7 , 8 , 9 , 10 , 107 ], and found that the maximum electrosorption capacity of MB for these carbon foams reached to 1846.7 mg/g when applying −1.2 V voltage. Under most conditions, the adsorption time of methyl orange (MO) solution using most water treatment methods is more than 1 h. Whereas, Liu and co-workers used the holey graphene hydrogel (R-HGH) prepared by one-step hydrothermal method as the CDI electrode [ 108 ].…”
Section: Applications Of Electrosorption Technology In Water Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this group synthesized porous MXene/SWCNTs film as a CDI electrode for the removal of organic dyes in wastewater ( Figure 5 f–j), and the maximum adsorption capacity was as high as 28,403.7 mg/g when applying −2.4 V voltage [ 106 ]. In addition, our group prepared carbon foam electrodes derived from waste cigarette filters/zeolitic-imidazolate frameworks-8 (ZIF-8) composites [ 6 , 7 , 8 , 9 , 10 , 107 ], and found that the maximum electrosorption capacity of MB for these carbon foams reached to 1846.7 mg/g when applying −1.2 V voltage. Under most conditions, the adsorption time of methyl orange (MO) solution using most water treatment methods is more than 1 h. Whereas, Liu and co-workers used the holey graphene hydrogel (R-HGH) prepared by one-step hydrothermal method as the CDI electrode [ 108 ].…”
Section: Applications Of Electrosorption Technology In Water Treatmentmentioning
confidence: 99%
“…Globally, water pollution has become a hot topic in recent years. In order to address this issue, chemical precipitation, membrane separation, ion exchange, distillation, adsorption and other technologies have been proposed by researchers [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. In general, ordinary adsorbents have been widely used in the field of water treatment due to the simple operation process.…”
Section: Introductionmentioning
confidence: 99%